A case series of pediatric patients with direct antiglobulin test negative autoimmune hemolytic anemia. Issue 8 (21st May 2019) - Miller, Jonathan; Cai, Wei; Andrews, Jennifer; Narla, Anupama
Abstract : BACKGROUND: The diagnosis of autoimmune hemolytic anemia (AIHA) can be challenging since the direct antiglobulin test (DAT) has been reported to be falsely negative in 3%‐11% of cases. In children with anemia, laboratory and/or clinical evidence of hemolysis and a negative DAT, clinicians should consider further specialized testing to confirm AIHA to accurately diagnose and treat this uncommon pediatric entity. STUDY DESIGN AND METHODS: A retrospective chart review was undertaken at a large tertiary care academic pediatric hematology practice to describe our experience with DAT‐negative AIHA. RESULTS: From January 1, 2010 through August 1, 2016, 10 children were described who had clinical and laboratory evidence of AIHA, a negative DAT, and further specialized serologic testing confirming this diagnosis. CONCLUSION: This case series highlights the need for further serologic workup when a child's clinical presentation is highly consistent with AIHA despite a negative DAT.